Research on the Influencing Factors of College Students’ Satisfaction with Labor Education - Chen, Shuyan (Transactions on Social Science, Education and Humanities Research, 2023)
Labor education is an indispensable link in the links of establishing morality and cultivating people, strengthening the country and enriching the people, and managing the country and government. Clarifying the factors affecting the satisfaction of college students on labor education is conducive to providing basic support for the further development of China’s labor education. Through literature review, it is found that differences in school location, nature, level and other aspects have different degrees of impact on satisfaction.